Analisis Perencanaan Persediaan Bahan Baku Pupuk dan Optimalisasi Kapasitas Gudang Bahan Baku - Erlangga Azam Ariputra; Siti Mundari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT. Dwi Jaya Ekaprima faces fluctuating raw material inventory that alternately causes overstock and shortage conditions, along with suboptimal warehouse capacity and layout. This study aims to analyze optimal raw material inventory planning and to design an improved warehouse layout. Data used include historical demand and consumption records of five raw materials throughout 2025. Methods applied include Single Exponential Smoothing (SES) for demand forecasting, Wagner-Whitin Algorithm and Silver-Meal Algorithm for optimal order quantity determination, and calculation of Safety Stock, Reorder Point (ROP), and total inventory cost analysis. The results indicate that SES with α = 0.9 is the best forecasting method, the Wagner-Whitin Algorithm yields the minimum total inventory cost, the highest ROP value belongs to Batu Pedel at 147,992 kg, and the Shared Storage method is selected as the proposed warehouse layout, optimizing a total storage area of 1,293.50 m² across three production warehouses without additional construction.